PERAN DAN URGENSI PENDIDIKAN ANTI KORUPSI DI KALANGAN MAHASISWA DALAM MENCEGAH TERJADINYA TINDAKAN KORUPSI - Irwansyah, Irwansyah (Al-Manba, 2023)
In the Ministry of Education and Culture Circular No. 1016/E/T/2012 which is the implementation of Presidential Instruction (Inpres) No. 55 of 2011 concerning actions to prevent and eradicate corruption within the Ministry of Education and Culture, is the basis for integrating anti-corruption education in Civic Education/Citizenship courses. With this, anti-corruption education has more roles and goals that make students the next generation. The involvement of individual students in the broad anti-corruption movement is the smallest point but also the most important and main in eradicating corruption. In a broader scope, student involvement is needed in the anti-corruption movement which aims to prevent massive and systematic corruption in society. Students with their competencies can become leaders in the mass anti-corruption movement whether local, national or even global.